Optimal two crop succession under limited resource condition a mixed integer goal programming to self-financed Kapatagan farmers in Kapatagan, Digos, Davao del Sur - Mag-usara, Eunice Mantilla (2008)
A mixed integer goal programming model on two-crop succession with three seasons was developed. It is a model that maximizes net income, maximizes working capital, minimizes chemical usage, and minimizes hired labor of farmer's subject to the available resources of the farmers. This model was applied to the six major crops planted in Kapatagan namely: (1) cabbage, (2) carrots, (3) Chinese cabbage, (4) corn, (5) potato, and (6) tomato. Analytical hierarchy process was used to obtain the weights of each goal. Since farmer's preferences differed, clustering was done to group them. Each group was studied separately. Under optimal land allocation, only the goal on maximizing organic fertilizer usage was highly violated. Farmers? preferences did not matter. The goal programming model that has been developed can aid Kapatagan farmers in land allocation for crops by offering flexibility in their decision-making